2023
DOI: 10.3390/cancers15041183
|View full text |Cite
|
Sign up to set email alerts
|

AI-Powered Diagnosis of Skin Cancer: A Contemporary Review, Open Challenges and Future Research Directions

Abstract: Skin cancer continues to remain one of the major healthcare issues across the globe. If diagnosed early, skin cancer can be treated successfully. While early diagnosis is paramount for an effective cure for cancer, the current process requires the involvement of skin cancer specialists, which makes it an expensive procedure and not easily available and affordable in developing countries. This dearth of skin cancer specialists has given rise to the need to develop automated diagnosis systems. In this context, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 122 publications
0
14
0
1
Order By: Relevance
“…Epidemiological and clinical investigations improved documentation of skin cancer incidence and prevalence, increasing discussion on prevention and detection. Literature has recognized the paramount importance of early detection and management for skin cancer and the potential for assistance by artificial intelligence (AI) tools at this stage ( 5 ). However, monitoring with survival analysis, along with discovery of survival markers are greatly needed for clinical prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and clinical investigations improved documentation of skin cancer incidence and prevalence, increasing discussion on prevention and detection. Literature has recognized the paramount importance of early detection and management for skin cancer and the potential for assistance by artificial intelligence (AI) tools at this stage ( 5 ). However, monitoring with survival analysis, along with discovery of survival markers are greatly needed for clinical prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…In dermatology, AI has the potential to reshape diagnostic processes using numerous imaging modalities including dermoscopy and sequential digital dermoscopy imaging (SDDI), wide-field clinical imaging and total body photography (TBP), reflectance cutaneous confocal microscopy (RCM), optical coherence tomography (OCT), line-field confocal OCT (LC-OCT), and lastly digital pathology. The majority of machine learning algorithms are commonly utilized for the analysis of single lesion dermoscopic images, with notable focus on the specific task of detecting melanoma ( 8 ). A landmark study by Esteva et al, reported higher accuracy for algorithms in classifying keratinocyte carcinoma and melanoma, compared to the average accuracy score from 16 expert dermatologists ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of AI-based approaches holds the potential to enhance accuracy and improve decision-making for melanoma management. Such models have the potential to facilitate detection enable initiation of appropriate treatment and contribute to effective strategies in managing melanoma [ 13 ]. The integration of AI-based detection models for melanoma and nevi into workflows can enhance capabilities, particularly in healthcare settings where access to specialized dermatologists or sufficient resources may be limited [ 14 ].…”
Section: Introductionmentioning
confidence: 99%